ผลของการใช้โปรแกรมการกำกับตนเองที่มีต่อคุณลักษณะอยู่อย่างพอเพียงของนักเรียนมัธยมศึกษาปีที่ 1 - ธันยพร มหาดิลกรัตน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
This study describes a quasi-experimental design that aimed to evaluate the effectiveness of a self-regulation program to promote sufficiency characteristics of eleventh grade students. Data were collected by 1) A sufficiency characteristic’s test, 2) An observed behaviors of sufficiency characteristic by a teacher, and 3) An observed behaviors of sufficiency characteristic by a student. One-way repeated measure ANOVA and t-test were employed for data analysis. Results showed (1) After participating a self-regulation program , pre-test, posttest and delayed-posttest scores of the sufficiency characteristic s test of experimental group students were not significantly different. (2) Experimental group students significantly received higher posttest scores of the sufficiency characteristic’s test than did control group students. And (3) Delayed-posttest scores of the sufficiency characteristic’s test of experimental group students and those of control group students were significantly different.